2004
DOI: 10.1029/2003ja010246
|View full text |Cite
|
Sign up to set email alerts
|

Sawtooth oscillations directly driven by solar wind dynamic pressure enhancements

Abstract: [1] We have examined four well-defined events of sawtooth oscillations in energetic particle flux and magnetic field at geosynchronous orbit. During all four events, nearly simultaneous energetic particle flux enhancements and magnetic field variations occurred at all MLTs for each sawtooth cycle. Geomagnetic H component data at low to middle latitude also show a global H increase simultaneously with the geosynchronous responses at all MLTs, and the northern and southern PC indices generally show increases at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
86
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(98 citation statements)
references
References 23 publications
8
86
1
3
Order By: Relevance
“…Both tests were not significant at the 5% level indicting a random occurrence in the number of events that occurred both within each hour and within the 3-h groupings. This is in line with findings by Lee et al (2004) that the solar wind pulse leads to a near simultaneous enhancement of the energetic flux at all MLT sectors at the geosynchronous orbit.…”
Section: Influence Of Local Time On Scasupporting
confidence: 80%
“…Both tests were not significant at the 5% level indicting a random occurrence in the number of events that occurred both within each hour and within the 3-h groupings. This is in line with findings by Lee et al (2004) that the solar wind pulse leads to a near simultaneous enhancement of the energetic flux at all MLT sectors at the geosynchronous orbit.…”
Section: Influence Of Local Time On Scasupporting
confidence: 80%
“…Lee et al [2004] suggest that the sawtooth oscillations of the geosynchronous magnetic field and energetic particle fluxes are very strongly associated with semiperiodic solar wind pressure pulses. …”
Section: Summary and Discussionmentioning
confidence: 99%
“…Lee et al (2004) examined four sawtooth events and discussed that the observed signatures are unlikely to be those of substorms and rather they are directly driven by solar wind pressure increases. Lyons et al (2005) also emphasised the importance of the dynamic pressure effect; they argued that the merging of the substorm component and pressure-driven component is essential for the wide azimuthal extents of the aurora and other signatures such as the current wedge.…”
Section: Electromagnetic Field Fluctuation At Themis-cmentioning
confidence: 99%